(untitled) - Marion Williams (Cambridge, New York, 1997)
The book presents an overview of educational psychology and discusses how different approaches to psychology have influenced language teaching methodology. Following this, four themes are identified: Recent psychological developments in each of these domains are discussed and implications are drawn for language teaching
Keywords: educational psychology,teachers - in-service training